Two-dimensional transition metal phosphorous trichalcogenides (MPX3): a review on emerging trends, current state and future perspectives. Issue 5 (24th December 2020) - Samal, Rutuparna; Sanyal, Gopal; Chakraborty, Brahmananda; Rout, Chandra Sekhar
Abstract : We review emerging trends and the state-of-the-art in 2D transition metal phosphorus chalcogenides (MPX3, X = S, Se), including their emergent applications, physicochemical properties and growth methodologies, and a perspective on future directions. Abstract : Profound scientific attention has been devoted to the expansive family of functional 2D materials soon after the isolation of graphene and the discovery of Dirac physics. Of particular note, the re-emergence of layer architecture metal thio(seleno) phosphate materials (MPX3, X = S, Se) materials with appreciable tunability in dimension and proximity on correlated ground states opened novel potential avenues for the ultimate theoretical (structural, magnetic) and realistic research. The wide spanned bandgap of 1.2–3.5 eV harnessed multifarious fundamental magnetic, electronic, ferroelectric, optical, intercalation properties and their prominent implementation in a plethora of applications, such as Li-ion batteries, field-effect transistors, visible and ultraviolet photodetectors, photo-electrochemical reactions and hydrogen (H2 ) storage. This review examines many of the scarcely touched aspects, such as multiple Dirac cones, vibrational properties, and responses in the presence of strain of MPX3 materials. In addition, the latest advancement in the emergent applications, physiochemical properties and assorted growth methodologies considering the palpable volume of research has been explored in detail in order to bring across a more complete discussion and outlook. We strongly believe that this review will be very handy for researchers working in various branches of science and engineering, such as physics, chemistry, materials science, and chemical engineering.